Zebrafish: Housing and husbandry recommendations. (June 2020) - Aleström, Peter; D'Angelo, Livia; Midtlyng, Paul J; Schorderet, Daniel F; Schulte-Merker, Stefan; Sohm, Frederic; Warner, Susan
This article provides recommendations for the care of laboratory zebrafish ( Danio rerio ) as part of the further implementation of Annex A to the European Convention on the protection of vertebrate animals used for experimental and other scientific purposes, EU Commission Recommendation 2007/526/EC and the fulfilment of Article 33 of EU Directive 2010/63, both concerning the housing and care of experimental animals. The recommendations provide guidance on best practices and ranges of husbandry parameters within which zebrafish welfare, as well as reproducibility of experimental procedures, are assured. Husbandry procedures found today in zebrafish facilities are numerous. While the vast majority of these practices are perfectly acceptable in terms of zebrafish physiology and welfare, the reproducibility of experimental results could be improved by further standardisation of husbandry procedures and exchange of husbandry information between laboratories. Standardisation protocols providing ranges of husbandry parameters are likely to be more successful and appropriate than the implementation of a set of fixed guidance values neglecting the empirically successful daily routines of many facilities and will better reflect the wide range of environmental parameters that characterise the natural habitats occupied by zebrafish. A joint working group on zebrafish housing and husbandry recommendations, with members of the European Society for Fish Models in Biology and Medicine (EUFishBioMed) and of the Federation of European Laboratory Animal Science Associations (FELASA) has been given a mandate to provide guidelines based on a FELASA list of parameters, 'Terms of Reference'.